2021
DOI: 10.1101/2021.04.19.21255738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of ABO blood group with COVID-19 severity, acute phase reactants and mortality

Abstract: Background and objectiveThe ABO blood group system has been associated with infectious and noninfectious disease, including dengue, hepatitis B virus (HBV), and severe respiratory syndrome coronavirus (SARS), etc. Coronavirus disease 2019 (COVID-19) is the ongoing pandemic with multitude of manifestations and association of ABO blood group in South-East Asian population needs to be explored.MethodsIt was a retrospective study of patients with real time polymerase chain reaction (RT-PCR) diagnosis of COVID-19 a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Furthermore, emerging studies have shown that ABO blood groups may also play a major role in the course of illness and in the outcome of COVID-19 patients; for example, COVID-19 was found to be less prevalent among people with blood group O. On the other hand, people with blood group A were more susceptible to acquiring COVID-19 with a higher mortality rate [9][10][11]. We used a well-crafted data sheet composed of five main sections: demographics, clinical features, vital signs, laboratory findings, and COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, emerging studies have shown that ABO blood groups may also play a major role in the course of illness and in the outcome of COVID-19 patients; for example, COVID-19 was found to be less prevalent among people with blood group O. On the other hand, people with blood group A were more susceptible to acquiring COVID-19 with a higher mortality rate [9][10][11]. We used a well-crafted data sheet composed of five main sections: demographics, clinical features, vital signs, laboratory findings, and COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 99%